HUMAS DALAM PERSPEKTIF ONTOLOGIS: TINJAUAN FUNGSIONAL MANAJEMEN HUMAS - Faiz, Faiz; Rahwiniyanto, Didik (JURNAL AL-TANZIM, 2019)
This paper aims to examine the functional review of public relations management from an ontology perspective. Public Relations is an organizational activity that is manifested in the form of activities and at the same time is a process of communication between one individual with an individual or a community. The communication process that occurs and is created in this activity, is very important for the smooth and sustainable organization. Therefore, an ontology approach is needed, as part of a philosophical study to dissect about public relations management in terms of its function. As part of the study of philosophy, ontology has a very important role in finding out what and to what extent public relations management is to be achieved. In this perspective, the study of the functional review of public relations management concerns matters that have an existence in the dimensions of space and time, and can be reached by sensory experience, which includes the phenomenon of public relations that can be observed, measured and can be obtained and can be interpreted, so that it can be drawn a conclusion. This study uses a qualitative research type library approach. The data analysis technique used is content analysis. The results of the study show that; the managerial functional review of public relations covers the activities of fact finding, planning, communication, actuating, and evaluating.